Modeling Intention-Based Critical Determinants of E-Commerce Utilization: Emerging Business Models and Transformation in the Digital World - Tong, Tianjie; Xiong, Yuyu (Frontiers in Psychology, 2022)
Companies in the world today understand that keeping users in touch is essential to enhancing their trust. The primary objective of this study is to determine the intention-based critical determinants of E-commerce utilization in China from the end users' perspective. We develop a framework that identifies the factors that influence E-commerce utilization in China. Besides, we introduce observational research (data analysis) conducted in a real-world E-commerce sense. Results are based on a sample of 400 respondents by employing a comprehensive questionnaire survey. The SEM/PLS approach was used to analyze the data. Study results show that perceived usefulness, perceived ease of use, reputation, trust in vendors, and purchase frequency significantly influence consumers' intention to use E-commerce systems. Research outcomes emphasize transforming social norms, raising consumers' awareness, redesigning policy frameworks, and highlighting the paybacks that E-commerce offers by integrative and consistent efforts.